Severity of hearing loss after platinum chemotherapy in childhood cancer survivors. Issue 9 (19th June 2022) - Strebel, Sven; Mader, Luzius; Sláma, Tomáš; Waespe, Nicolas; Weiss, Annette; Parfitt, Ross; am Zehnhoff‐Dinnesen, Antoinette; Kompis, Martin; von der Weid, Nicolas X.; Ansari, Marc; Kuehni, Claudia E.
Abstract: Background: Hearing loss is a potential side effect from childhood cancer treatment. We described the severity of hearing loss assessed by audiometry in a representative national cohort of childhood cancer survivors (CCS) and identified clinical risk factors. Procedure: We included all CCS from the Swiss Childhood Cancer Registry who were diagnosed ≤18 age and treated with platinum‐based chemotherapy between 1990 and 2014. We extracted audiograms, treatment‐related information, and demographic data from medical records. Two reviewers independently assessed the severity of hearing loss at latest follow‐up using the Münster Ototoxicity Scale. We used ordered logistic regression to identify clinical risk factors for severity of hearing loss. Results: We analyzed data from 270 CCS. Median time from cancer diagnosis to last audiogram was 5 years (interquartile range 2.5–8.1 years). We found 53 (20%) CCS with mild, 78 (29%) with moderate, and 75 (28%) with severe hearing loss. Higher severity grades were associated with (a) younger age at cancer diagnosis (odds ratio [OR] 5.4, 95% confidence interval [CI]: 2.5–12.0 for <5 years); (b) treatment in earlier years (OR 4.8, 95% CI: 2.1–11.0 for 1990–1995); (c) higher cumulative cisplatin doses (OR 13.5, 95% CI: 4.7–38.8 for >450 mg/m 2 ); (d) concomitant cranial radiation therapy (CRT) (OR 4.4, 95% CI: 2.5–7.8); and (e) hematopoietic stem cell transplantation (HSCT) (OR 2.7, 95% CI: 1.0–7.2). Conclusion: Three of four CCS treated with platinum‐based chemotherapy experienced some degree of hearing loss. We recommend closely monitoring patient's hearing function if treated at a young age with high cumulative cisplatin doses, and concomitant CRT as part of long‐term care.